2014
DOI: 10.1021/am500912m
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Transfer by Gold Nanoparticle at DNA Modified Electrode and Its Application to Label-Free DNA Detection

Abstract: Rational utilization of nanomaterials to construct electrochemical nucleic acid sensors has attracted large attention in recent years. In this work, we systematically interrogate the interaction between gold nanoparticles (GNPs) and single-strand DNA (ssDNA) immobilized on an electrode surface and then take advantage of the ultrahigh charge-transfer efficiency of GNPs to develop a novel DNA sensing method. Specifically, ssDNA modified gold electrode can adsorb GNPs because of the interaction between gold and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…The decrease in curves c and d can be explained by the fact that AuNPs assembled onto the electrode surface facilitate the electron transfer of ferricyanide. 66,67 When the electrode was incubated with PKA (curve e), a slight increase in R et was observed. This indicated that the formation of IP 20 -PKA complexes on the sensor surface caused a barrier for the electron transfer of ferricyanide.…”
Section: Electrochemical Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…The decrease in curves c and d can be explained by the fact that AuNPs assembled onto the electrode surface facilitate the electron transfer of ferricyanide. 66,67 When the electrode was incubated with PKA (curve e), a slight increase in R et was observed. This indicated that the formation of IP 20 -PKA complexes on the sensor surface caused a barrier for the electron transfer of ferricyanide.…”
Section: Electrochemical Analysismentioning
confidence: 97%
“…The unique electrical properties of AuNPs may lead to a significant decrease in the charge transfer resistance. 66,67 When the Fc-peptide was used in this design, the network of AuNPs/ Fc-peptide on the electrode surface would exhibit an amplified voltammetric signal from the electrochemical oxidation of Fc tags. However, when the electrode was covered with PKA, IP 20 immobilized on the electrode surface would lose its ability to trigger the formation of AuNPs-based network architecture due to the formation of IP 20 -PKA complex.…”
Section: Principle Of Electrochemical Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The AuNPs based colorimetric methods are usually developed based on enzyme-mimic activities, interparticle cross-linking or a destabilization induced aggregation mechanism. Our group has also proposed series of AuNPs based biosensor for detection of DNA [21][22][23], metal ions [24,25], proteins [26,27], bioactive molecules [28,29] and cancer markers [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence-specific detection of DNA has been reported for playing an important role in the precaution of genetic or pathogenic diseases, treatment of viral and bacterial infections, and prognosis of cancer [1,2]. Therefore, ultrasensitive and selective detection of DNA has attracted particular attention [3].…”
Section: Introductionmentioning
confidence: 99%